Complex Sciences Second International Conference, COMPLEX 2012, Santa Fe, NM, USA, December 5-7, 2012, Revised Selected Papers - Glass, Kristin; Colbaugh, Richard; Ormerod, Paul.; Tsao, Jeffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on Complex Sciences, COMPLEX 2012, held in Santa Fe, New Mexico, USA in December 2012. The 29 revised full papers presented were carefully reviewed and selected from various submissions. The papers cover aspects on foundations and analysis of complex systems, complex biological systems, complex social systems, complex engineering systems.
The Crossover Point: Comparing Policies to Mitigate Disruptions -- Progress Curves and the Prediction of Significant Market Events -- Bifurcation as the Source of Polymorphism -- Large-Scale Conflicts in Massively Multiplayer Online Games -- Impact of Global Edge-Removal on the Average Path Length -- Assessing the Spatial Impact on an Agent-Based Modeling of Epidemic Control -- Behaviors of Actors in a Resource-Exchange Model of Geopolitics -- Portfolio Optimization and Corporate Networks: Extending the Black Litterman Model -- Cooperation through the Endogenous Evolution of Social Structure -- To Trade or Not to Trade: Analyzing How Perturbations Travel in Sparsely Connected Networks -- Paid Sick-Leave: Is It a Good Way to Control Epidemics? -- Decoding Road Networks into Ancient Routes: The Case of the Aztec Empire in Mexico -- A Policy of Strategic Petroleum Market Reserves -- Identifying Critical Infrastructure Interdependencies for Healthcare Operations during Extreme Events -- Modeling Emergence in Neuroprotective Regulatory Networks -- Identification of Chordless Cycles in Ecological Networks.
Keywords: Computer science; Information theory; Computational complexity; Artificial intelligence; Computer simulation; Computer Science; Simulation and Modeling; Complex Systems; Artificial Intelligence (incl. Robotics).; Theory of Computation; Discrete Mathematics in Computer Science